allegansveritatem
Full Member
- Joined
- Jan 10, 2018
- Messages
- 962
Consider the function \(\displaystyle y=f(x)=(x^3-1)\).What is the difference between these two expressions. Is this just two different ways of referring to the same thing?
View attachment 12631
I will have to go over this a few times to get exactly what you are saying here. When you say "apply the function" I guess you mean perform the operations inside the abs value symbol and then take the positive of the result?So the first applies to the whole function and the second only to the x element?Not at all.
The first says that you first apply the function f, and then take the absolute value of the result.
The second says that you first take the absolute value of x, then apply f to the result.
For example, if we take f(x) = 3x + 2, then
The two functions are compositions of f(x) and abs(x), and composition is not commutative: Changing the order results in different functions.
- |f(x)| = |3x + 2|, and |f(-1)| = |-1| = 1; but
- f(|x|) = 3|x| + 2, and f(|-1|) = f(1) = 3(1) + 2 = 5.
I am having my nightly near-death experience but in the morning I will go over your post and parse it. I think it will help clarify the situation. Thanks.Consider the function \(\displaystyle y=f(x)=(x^3-1)\).
\(\displaystyle f(-2)=(-2)^3-1=-8-1=-9\) so \(\displaystyle |f(-2)|=9\) BUT
\(\displaystyle f(|x|)=(|x|^3-1)\) so \(\displaystyle f(|-2|)=(|-2|^3-1)=7\)
Apply the function (namely, f) means "do what it says". The function f in my example says, "triple the input and add 2". So when we apply the function to the input -1, we triple it (-3) and add 2 (making -1): f(-1) = -1.I will have to go over this a few times to get exactly what you are saying here. When you say "apply the function" I guess you mean perform the operations inside the abs value symbol and then take the positive of the result?So the first applies to the whole function and the second only to the x element?
Got it. I think my problem had something to do with the way my book refers to functions as f(x) no matter what the actual function may be. I am not used to that convention.Apply the function (namely, f) means "do what it says". The function f in my example says, "triple the input and add 2". So when we apply the function to the input -1, we triple it (-3) and add 2 (making -1): f(-1) = -1.
That's common. Your book probably refers to inputs as x, too, no matter what the actual input may be.… book refers to functions as f(x) no matter what the actual function may be …